Questioning the Direction of the Qibla of the Omba Public Cemetery, Mamben Daya Village, East Lombok Regency - Sona, Wahyu Abdul Muttakin; Sado, Arino Bemi; Taufikurrahman, Arief (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
This study investigates two primary issues: the causes of the misalignment of the qibla direction at the Omba Public Cemetery in Mamben Daya Village and the formulation of appropriate solutions to ensure that the qibla direction is determined in an orderly and precise manner under Islamic law. Employing field research with a qualitative descriptive approach, data were collected through structured measurements, direct field observations, and interviews with key informants. The findings indicate that local authorities lack sufficient knowledge of accurate techniques for determining the qibla direction for burials. Furthermore, the challenges identified can be addressed by implementing formal regulations established by the village government to enhance community awareness and ensure the accurate alignment of graves with the qibla direction.